Amino Acid, Fatty Acid and Physico-Chemical Analyses of Jatropha curcas (Physic Nut) Seed Flour and Oil - Olaofe, O; Faleye, FJ; Abey, JA (Bangladesh Journal of Scientific and Industrial Research, 2011)
The amino acid of seed flour and fatty acid and physico-chemical analysis of oil both from Jatropha curcas (physic nut) seed were analytically determined. Amino acid results showed that the protein contained nutritionally useful quantities of most of the essential amino acids including sulphur-containing amino acids. The crude protein content was 34.2%. The total essential amino acid (TEAA) with histidine was 32.7g /100g while the TEAA without histidine was 30.6g /100g protein. Glutamic acid (16.8 g/100g protein) was found to be the most abundant amino acid followed by aspartic acid (9.2 g/100g protein) in the seed flour. The seed oil of Jatropha curcas has a high crude fat content of 46.1% and a high proportion of total unsaturated fatty acid (40.8%) with liloleic (18:2) as the most abundant unsaturated fatty acid while the total saturated fatty acid was 8.61% Palmitic acid (16:0), 8.6 % was found to be the most abundant saturated fatty acid. The values for the physico-chemical properties of the extracted oil were: Acid value, (4.62 mgKOH/g), iodine value, (96.0 mgI2/g), peroxide value, (6.22 mgO2/g), saponification value, (219 mg KOH/g), specific gravity, (0.89) and refractive index, (1.46), These results suggest that Jatropha curcas is useful in some food formulations. Key words:. DOI: 10.3329/bjsir.v45i4.7379 Bangladesh J. Sci. Ind. Res. 45(4), 345-350, 2010